Home-country Internet and Immigrants' Well-being - Alexander Yarkin (Global Labor Organization (GLO), 2025)
This paper documents the effects of home-country Internet expansion on immigrants' health and subjective well-being (SWB). Combining data on SWB and health from the European Social Survey (ESS) with data on 3G and overall Internet expansion (ITU and Collins Batholomew), I find that immigrants' SWB and health increase following home-country Internet expansion. This result is observed in both the TWFE, and event study frameworks. The effects are stronger for (i) first-generation immigrants, (ii) those less socially integrated at destination, and (iii) those with stronger family ties to the origins. Thus, while recent evidence points towards negative effects of the Internet and social media on user well-being, the effects are very different for immigrants.
Keywords: 330; Immigration; Internet; Subjective Well-being; Health; Social Networks